Fracture of Implant Prosthesis at Abutment Neck- A Rare Phenomenon - Vasantha Vijayaraghavan; Priya Lele; Rupali Patil; Darshana Mundhe (Institute of Medico-legal Publications Pvt Ltd, 2021)
Implant dentistry has become common treatment modality for total and partial edentulous arches.Complications arising after placement and eventual functioning of implant prosthesis are also increasinglyencountered in routine clinical practice. This case report is about implant prosthesis where fracture of neckof abutment occurred at internal hex level of implant after 5 years of optimal functioning in oral cavity.